Effects of High-Frequency Transcranial Magnetic Stimulation for Cognitive Deficit in Schizophrenia: A Meta-Analysis - Jiang, Yi; Guo, Zhiwei; Xing, Guoqiang; He, Lin; Peng, Haitao; Du, Fei; McClure, Morgan A.; Mu, Qiwen (Frontiers in Psychiatry, 2019)
Objective: Repetitive transcranial magnetic stimulation (rTMS) has been applied to dorsolateral prefrontal cortex (DLPFC) to improve cognitive function of patients with schizophrenia (SZs). The aim of this meta-analysis was to evaluate whether a high-frequency rTMS course could enhance cognitive function in SZs. Methods: Studies published in PubMed, Cochrane Library, Embase, ScienceDirect, and Web of science were searched until April 2018. The search terms include: ‘repetitive transcranial magnetic stimulation’ or ‘rTMS’, ‘SZ’ or ‘schizophrenia’, and ‘neurocognition’ or ‘neurocognitive performance’ or ‘cognitive effects’ or ‘cognitive’. After screening the literatures according to inclusion and exclusion criteria, extracting data, and evaluating the methodological quality of the included studies, a meta-analysis was performed using RevMan 5.3 software (The Cochrane Collaboration, USA). Results: A total of 9 studies on cognitive dysfunction of SZs were included and involved 351 patients. A significant efficacy of high-frequency rTMS on working memory in SZs was found compared to sham stimulation (p=0.009, SMD = 0.34). Specifically, rTMS treatment positioned on the left DLPFC, with a total pluses less than 30000 is more significantly more effective in improving the working memory (SMD = 0.33, p = 0.03). No improvement was found in other cognitive processes such as executive function, attention, processing speed, and language function. For the follow-up observations, high-frequency rTMS has long-lasting sustained effects on working memory (SMD = 0.45, p = 0.01) and language function (SMD = 0.77, p = 0.02) in SZs. Conclusions: High rTMS over the left DLPFC with a total pulses less than 30,000 stimulation could significantly improve working memory in SZs for an extended period of time.